2002
DOI: 10.1021/jo016131f
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of N-Aryl Pyrroles via Cu(II)-Mediated Cross Coupling of Electron Deficient Pyrroles and Arylboronic Acids

Abstract: N-Arylation of electron-deficient pyrroles has been achieved by cross-coupling with arylboronic acids at room temperature in the presence of stoichiometric amounts of copper(II) acetate. The generality of this reaction has been established with variously substituted pyrroles as well as boronic acids. A key intermediate in the synthesis of a matrix metalloprotease inhibitor has been achieved using this methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 12 publications
(11 reference statements)
1
36
0
1
Order By: Relevance
“…[38] In general these molecular motifs appear to be excellent substrates for N-arylation reactions, and in nearly all cases high yields of the products 90-95 were obtained (Scheme 16). However, the reaction times ranged from 2-13 days, but generally were in the 2-day range (Scheme 16).…”
Section: Applications: Medicinal Chemistry and Solid-phasementioning
confidence: 99%
“…[38] In general these molecular motifs appear to be excellent substrates for N-arylation reactions, and in nearly all cases high yields of the products 90-95 were obtained (Scheme 16). However, the reaction times ranged from 2-13 days, but generally were in the 2-day range (Scheme 16).…”
Section: Applications: Medicinal Chemistry and Solid-phasementioning
confidence: 99%
“…Pyrrole has also been N-arylated with an aryl iodide using CuI/trans-1,2-cyclohexanediamine in the presence of K 3 PO 4 as the catalytic system [576]. 2-Acetylpyrrole, as well as pyrrole-2-carboxaldehydes possessing an additional electron-withdrawing substituent at C4, undergoes efficient N-arylation with arylboronic acids at ambient temperature using stoichiometric amounts of Cu(OAc) 2 [577]. Treatment of pyrroles with vinyl triflates in the presence of the system Pd 2 (dba) 3 /Xphos/K 3 PO 4 constitutes a new route to 1-vinylpyrroles [578].…”
Section: Transition Metal Catalyzed Coupling Reactionsmentioning
confidence: 99%
“…However, Mederski [31], and Srirangam and co-workers [32] showed that N-arylation proceeded in good yields when there is a chelating aldehyde, ketone or ester alpha to the NH group. In contrast, for phenylalanine, which has an α-carboxylate group, no N-arylation was observed indicating that the α-carboxylate has a deleterious effect, probably due to tight binding to the copper center [23a, b].…”
Section: C-n (Heteroarene) Cross-couplingmentioning
confidence: 99%